Zdrowie i choroba w Prusach 1871-1918 = Health and Illness in Prussia in 1871-1918 - Łukasiewicz, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The second half of the 19th century was a time when industrialisation accelerated in Germany, particularly in the west of Prussia, Berlin and Silesia. Large urban centres developed rapidly, densely populated by labourers whose housing conditions were largely inadequate and their wages insufficient. Business owners, town councils as well as state authorities noticed the growing risk of an epidemic and increasing social unrest which could lead to bloodshed.
Keywords: Szpital; Prusy; epidemie; położne; lekarze; hospital; Prussia; epidemic; midwife; doctor